Signatures of Magnetic Flux Ropes in the Low Solar Atmosphere Observed in High Resolution - Wang, Haimin; Liu, Chang (Frontiers in Astronomy and Space Sciences, 2019)
Magnetic flux ropes (MFRs) are important physical features closely related to solar eruptive activities with potential space weather consequences. Studying MFRs in the low solar atmosphere can shed light on their origin and subsequent magnetic structural evolution. In recent years, observations of solar photosphere and chromosphere reached a spatial resolution of 0.1 to 0.2 arcsec with the operation of meter class ground-based telescopes, such as the 1.6m Goode Solar Telescope at Big Bear Solar Observatory and the 1m New Vacuum Solar Telescope at Yunnan Observatory. The obtained chromospheric Halpha filtergrams with the highest resolution thus far have revealed detailed properties of MFRs before and during eruptions, and the observed pre-eruption structures of MFRs are well consistent with those demonstrated by nonlinear force-free field extrapolations. There are also evidences that MFRs may exist in the photosphere. The magnetic channel structure, with multiple polarity inversions and only discernible in high-resolution magnetograph observations, may be a signature of photospheric MFRs. These MFRs are likely formed below the surface due to motions in the convection zone and appear in the photosphere through flux emergence. Triggering of some solar eruptions is associated with an enhancing twist in the low-atmospheric MFRs.